Analysis of H-2 determinants recognized during the induction of H-Y-immune cytotoxic T cells by monoclonal antibodies in vitro - Brenan, M (The Rockefeller University Press, 1981)
Monoclonal antibodies directed to the D region of H-2(k) when present during in vitro culture inhibit the generation of CBA/H and C3H.H-2(o) H-Y-immune cytotoxic T cells . Monoclonal antibodies directed to the I-A(k) and I-E(k) region specifically inhibited induction of CBA/H H-Y-immune cytotoxic T cells only when they were present simultaneously in culture. These findings show T helper cell requirement for CBA/H H-Y-immune cytotoxic T cell induction, and suggest that two I region-coded restriction antigens for T helper cells are involved.